1982
DOI: 10.1128/aac.22.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro activities of azlocillin-cefotaxime and azlocillin-tobramycin combinations against blood and multi-drug resistant bacterial isolates

Abstract: The in vitro activities of azlocillin and cefotaxime in combination and of azlocillin and tobramycin in combination against 100 blood isolates and 50 multidrug-resistant isolates were compared. With both combinations, antibacterial spectrums were complementary. Although synergy against individual strains was infrequently observed (except for azlocillin-cefotaxime against Streptococcus faecalis and azlocillin-tobramycin against Pseudomonas aeruginosa), 97% of blood isolates and 76% of multidrug-resistant isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Consistent with the P. aeruginosa in vitro studies, synergy was commonly observed with dual beta-lactam combination regimens that included aztreonam (Buesing and Jorgensen, 1984;Sader et al, 2003;Stutman et al, 1984) or a third-generation cephalosporin (Buesing and Jorgensen, 1984;Daschner and Hoffmann, 1982;Tsuchiya, 1981a, 1981b;Kurtz et al, 1981;Miles et al, 1981;Neu, 1982;Sader et al, 2003;Verbist and Verhaegen, 1984;Zinner et al, 1981). Combinations including mecillinam were also found to be highly successful against Enterobacteriaceae in earlier analyses, where synergistic interactions were observed against a high proportion of all pathogens (Anderson et al, 1981;Baltimore et al, 1976;Chattopadhyay and Hall, 1979;Cleeland and Squires, 1983;Fass, 1980Fass, , 1982aFass, , 1982bTsuchiya, 1981a, 1981b;Schaad et al, 1982;Scheld et al, 1979;Tybring and Melchior, 1975;van der Voet et al, 1983). In more recent studies, carbapenems were synergistic when used with another beta-lactam.…”
Section: Enterobacteriaceae Sppsupporting
confidence: 57%
See 2 more Smart Citations
“…Consistent with the P. aeruginosa in vitro studies, synergy was commonly observed with dual beta-lactam combination regimens that included aztreonam (Buesing and Jorgensen, 1984;Sader et al, 2003;Stutman et al, 1984) or a third-generation cephalosporin (Buesing and Jorgensen, 1984;Daschner and Hoffmann, 1982;Tsuchiya, 1981a, 1981b;Kurtz et al, 1981;Miles et al, 1981;Neu, 1982;Sader et al, 2003;Verbist and Verhaegen, 1984;Zinner et al, 1981). Combinations including mecillinam were also found to be highly successful against Enterobacteriaceae in earlier analyses, where synergistic interactions were observed against a high proportion of all pathogens (Anderson et al, 1981;Baltimore et al, 1976;Chattopadhyay and Hall, 1979;Cleeland and Squires, 1983;Fass, 1980Fass, , 1982aFass, , 1982bTsuchiya, 1981a, 1981b;Schaad et al, 1982;Scheld et al, 1979;Tybring and Melchior, 1975;van der Voet et al, 1983). In more recent studies, carbapenems were synergistic when used with another beta-lactam.…”
Section: Enterobacteriaceae Sppsupporting
confidence: 57%
“…Moxalactam and first-generation cephalosporins, such as cefazolin and cephalothin, were also found to be antagonistic when combined with other beta-lactams (Buesing and Jorgensen, 1984;Fass, 1982aFass, , 1982bFu and Neu, 1978;Kuck et al, 1981;Neu and Fu, 1978;Verbist and Verhaegen, 1984). An exception to this was found when these agents were combined with mecillinam.…”
Section: Enterobacteriaceae Sppmentioning
confidence: 79%
See 1 more Smart Citation
“…Antibiotic therapy may lead to selection of pre-existing mutant resistent organisms. Combinations of antibiotics, or periodical changes in regimens may reduce the occurrence of such resistance [9,21,50,92].…”
Section: General Considerationsmentioning
confidence: 99%
“…1982;Coppens & Klastersky, 1979;Eliopoulos & Moellering, 1982;Fass, 1982;Greenwood & Eley, 1982;Hoogkamp-Korstanje, Pot & Westerdaal, 1981;Slack, 1981;Tselentis et al. 1981;White, Comber & Sutherland, 1980;White et al.…”
Section: Introductionmentioning
confidence: 99%